Lectura crítica de las teorías más representativas de la ciencia del paisaje - Cancer Pomar, Luis (Geographicalia, 2017)
This work analyses the differents theories about the landscape science, which have most interest and followers at the present. We have a critical approach to them and, finally, we deduce that a lot of times they are totally compatibles, and even complementaries.